Are there differences between methods used for the objective estimation of boar sperm concentration and motility? - Sevilla, Francisco; Soler, Carles; Araya-Zúñiga, Ignacio; Barquero, Vinicio; Roldan, Eduardo R. S.; Valverde-Abarca, Anthony (My University, 2023)
Estimation of seminal quality can be carried out by examining different pa rameters. Such parameters directly influence the preparation of seminal doses used in artificial insemination in pigs. Sperm motility and concentration are relevant parameters in this context. The precision and accuracy of estimation of these parameters could thus contribute considerably to the productive performance of the pig industry. However, differences between systems could cause variations in estimates. These can be explained by the ability of the evaluator, type of sys tem, or calibration, among others. In this study, we used iSperm®, ISAS® v1, Open CASA v2, and the Accuread® photometer system to compare assessments of motility and sperm concentration. Bayesian analyses were used, and differences were found between the four methods of concentration estimation. Additional analyses revealed differences in estimates of motility using these systems.
Animals, vol. 13, no. 1622 (May, 2023):1-16
Keywords: Jabalí; Reproducción animal; Espermatozoides - Motilidad; Inseminación artificial